Factors Determining the Increased Risk of Falls in Individuals With Knee Pain in the Malaysian Elders Longitudinal Research (MELoR) Study - Mat, Sumaiyah; Razack, Azad Hassan; Lim, Jasmine; Khong, Su-Yen; Kamaruzzaman, Shahrul Bahyah; Chin, Ai-Vyrn; Abbas, Azlina Amir; Hairi, Noran Naqiah; Othman, Sajaratulnisah; Tan, Maw Pin (Frontiers in Medicine, 2019)
Objectives: While the negative impact of falls in older persons has been recognized, the association between knee pains and falls remains inconclusive due to underreporting and undertreatment of knee pain. This study was conducted to evaluate the relationship between knee pain and knee pain severity with falls risk and to further determine factors which influence this potential relationship. Design This was cross-sectional study from the Malaysian Elders Longitudinal Research (MELoR) study Setting Urban community dwellers in a middle-income South East Asian country. Participants 1212 of a representative sample of community dwelling older persons aged 55 years and older. Outcome measures Falls in the preceding 12 months and knee pain were collected during a home-based computer-assisted interview. Physical and functional performance were measured using the Timed Up and Go test and the Katz and Lawton scales respectively. Psychological status was determined using the Depression Anxiety and Stress Scale (DASS-21). Results Of the 1212 participants included in this analysis, knee pain was present in 402 (33.17%) individuals (124 (30.85%) mild, 210 (52.24%) moderate, 68 (16.92%) severe). The presence of knee pain was associated with increased risk of falls [odds Ratio, OR(95% confidence interval, CI): 1.81 (1.37-2.38)]. Severe knee pain was an independent predictor for falls after adjustment for functional impairment and psychological status. Mild, moderate and severe knee pain had a specific indirect effect on falls through reducing functional impairment, which in turn increases their psychological concern. Conclusion Future studies should explore this relationship prospectively and evaluate whether interventions which alleviate psychological concerns and improve function will reduce falls risk in those with mild to moderate knee pain.